The Effect of Kind of Manure with Stale Rice and Onion Extra Biovactors on Growth and Production of Waxy Purple Corn (Zea mays var. ceratina Kulesh): Pengaruh Macam Kotoran Ternak dengan Bioaktivator Nasi Basi dan Ekstrak Bawang Merah Terhadap Pertumbuhan dan Hasil Jagung Pulut Ungu (Zea mays var. ceratina Kulesh) - Nugroho, Wempy; Podesta, Fiana; Suryadi, Suryadi; Fitriani, Dwi; Yawahar, Jon (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to find out the interaction and effect of various kinds of manure with stale rice bioactivator and red onion extract. This study was conducted in Tanjung Perdana Village, Pondok Kubang District, Central Bengkulu Regency, Bengkulu Province. The design used was Completely Randomized Design (RAK) treatment 1, which was manure with stale rice bioactivator A0 (Control), A1 (Chicken Manure), A2 (Goat Manure), A3 (Cow Manure). The second treatment was red onion extract B0 (Control), B1 (0.75 ml/l), B2 (1.5 ml/l), B3 (2.25 ml/l). Each treatment was repeated 3 times in order to obtain 48 experimental units with 3 plants in each experimental unit so that 144 plants were obtained. The result indicated that various types of manure treatment with stale rice bioactivator had no significant effect of all abserved parameters. The treatment red onion extract had a very significant effect on cob length and significantly effected stem diameter 56 DAP, plant wet weight, and plant dry weight. Meanwhile, in this study, there was no interaction between various types of manure treatment with stale rice bioactivator and red onion extract on all observed parameters.